Sikap Traveller terhadap Promosi Tiket.com: Perspektif Tri-Component Attitude Model - Lady Faerrosa; L. Jatmiko Jati; Ika Yuliana (Target : Jurnal Manajemen Bisnis, 2023)
Marketing literacy has proven a lot that consumer attitudes influence their buying behavior. Therefore, research on consumer attitudes is one of the interesting studies. Marketers are competing to issue certain products or promos that can influence consumer attitudes. This study aims to examine the attitude of travelers in the perspective of the tri-component attitude model towards the Gledek price promo and the OTW promo issued by Tiket.com, specifically at the end of 2022. This study uses a qualitative approach where data is collected and analyzed using netnography methods. Researchers collected and analyzed relevant data posted by International Backpacker members on the Facebook platform in October-November 2022, namely 27 posts. The results showed that consumers gave a positive attitude towards the promo, both from a cognitive, affective, and conative perspective. The results of this research are expected to be a reference for companies, brands and small-scale businesses in creating promos that are of value to their consumers so as to influence their purchasing behavior. The results of this study also enrich previous research and are able to provide references for future researchers on similar topics.